Timely initiation of complementary feeding practices and associated factors among children aged 6–23 months in Dessie Zuria District, Northeast Ethiopia: a community-based cross-sectional study - Abate, Anteneh Demelash; Hassen, Seid Legesse; Temesgen, Minwuyelet Marru (Frontiers in Pediatrics, 2023)
Introduction: Ethiopia has one of the highest infant and child mortality rates in the world. From the age of six months, breast milk alone is no longer sufficient to cover all nutritional requirements. Complementary feeding must therefore begin at the age of six months. Infant and young child nutrition is a critical factor in human health, nutrition, survival, growth and development. Therefore, the aim of this study was to evaluate the timely initiation of complementary feeding practices and associated factors in children aged 6 to 23 months in the Dessie Zuria District. Methods: A community-based cross-sectional study design was used from March 16-30, 2019. The study included 770 mother-child pairs aged 6 to 23 months. A multistage sampling method was used to choose the study participants. Using a simple random sampling technique, 9 kebeles in the district were selected from a total of 31,, and from 103 Gotts or villages 31 were selected with 770 HHs out of 2329 HHs with children aged 6 to 23 months. Data were collected using a pretested semi-structured interviewer-administered questionnaire, which was then entered into Epi Data version 3.1 statistical software before being transferred to SPSS version 21 for further analysis. To summarize the data, descriptive statistics were used, which included a simple frequency table and figures. To evaluate factors, bivariate, and multivariable logistic regression were used. A p-value of less than 0.05 was used to determine statistical significance. Result: The percentage of children who started complementary feeding practices on time was 70.9%. Maternal occupation [AOR = 5.51, 95% CI: 1.61 -18.81], radio availability [AOR = 2.03, 95% CI: 1.32 - 3.12], Antenatal care follow-up [AOR = 6.19, 95% CI: 4.08 - 9.40], Place of delivery [AOR = 5.06%, CI: 3.34 - 7.68] and Postnatal care follow up [AOR = 4.32, 95% CI: 2.77- 6.72] were found factors of timely initiation of complementary feeding. Conclusion: When compared to WHO cut-off points, timely initiation of complementary feeding practice was relatively low. Maternal occupation, radio availability, ANC follow-up, place of delivery, and post-natal care visit were all significantly associated with the timely initiation of complementary feeding.